Para-type fully aromatic copolyamide particles and method for producing the same
Through the combination of para-type all-aromatic copolyamide of a specific structure and ionic liquid, the fibers are converted into small-molecular-scale particles with heat and shear force, solving the problem of difficult to produce particles in the prior art that are difficult to produce high thermal stability and good handling, and achieving an efficient and environmentally friendly production process.
Patent Information
- Application Number
- JP2023151893
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
The prior art is difficult to effectively produce small-molecular-scale para-type all-aromatic copolyamide particles with high thermal stability and good treatment properties, and traditional methods have problems of high cost and safety risks.
Using para-type all-aromatic copolyamides with specific structures, the fibers are converted into 5 to 500 nanometer particles by combining with ionic liquids, and precipitated by water or alcohol as a poor solvent.
The production of para-type all-aromatic copolyamide particles with high thermal stability and good handling properties has been achieved, which reduces the environmental burden and safety risks in the production process, and improves the recycling of materials.
Smart Images

Figure 2025044366000001 
Figure 2025044366000002 
Figure 2025044366000003
Abstract
Description
[Technical field]
[0001] The present invention relates to para-type wholly aromatic copolyamide particles and a method for producing the same, and more particularly to fine para-type wholly aromatic copolyamide particles having an average particle size of less than 500 nm. [Background technology]
[0002] It is known that nanoscale materials exhibit properties different from those of bulk size, and nanoscale ultrafine fibers have been studied for polyester fibers, carbon fibers, cellulose fibers, etc. In recent years, ultrafine fibers have also been studied for fully aromatic polyamide fibers, in contrast to cellulose, which does not have heat resistance.
[0003] As a method for producing these nano-scale ultrafine fibers, in the case of polyester, two kinds of polymers are used to obtain a two-component fiber consisting of a sea component and an island component, and then melt spinning or blend spinning using a technique such as extracting the sea component with a solvent or decomposing it with an alkali is carried out.
[0004] On the other hand, in the case of solution spinning using a solvent, methods for directly obtaining nonwoven fabrics using methods such as electrospinning are being considered. On the other hand, in the case of cellulose, in order to break the intermolecular hydrogen bonds of the raw material wood flour or pulp, a technology is used in which the raw material is subjected to chemical treatment and then mechanically beaten with a refiner, etc. However, cellulose does not have high heat resistance, and there has been a demand for ultrafine fibers made of heat-resistant materials.
[0005] Therefore, for heat-resistant para-type wholly aromatic polyamides, a technique for fibrillating and nano-sizing fibers by blasting dry ice or liquefied carbon dioxide onto the fibers has been studied in JP 2011-168931 A (Patent Document 1) and the like. However, this method only fibrillates the surface of the fibers, and does not fibrillate the inside.
[0006] Therefore, in order to break the intermolecular hydrogen bonds of para-type wholly aromatic polyamide fibers, which are said to be insoluble in solvents, a study has been conducted in JP-T-2019-511387 (Patent Document 2) and the like to obtain aramid nanofibers by immersing the fibers in a solution in which a strong alkali such as potassium hydroxide is dissolved in an organic solvent. In this method, it is necessary to replace the ultrafine fibers obtained in the solvent with water to improve handling. Therefore, it is necessary to recover the strongly alkaline organic solvent used to dissolve the para-type wholly aromatic fibers and the poor solvent such as water or alcohol-based solvent used for solvent replacement, which increases costs and is economically unreasonable. In addition, it is necessary to handle a strong alkaline solution, and great consideration must be given to safety in the working environment. Furthermore, these nanomaterials have a high aspect ratio, and when the fibers are assembled, voids are formed due to steric hindrance, so the density decreases and the expected nanoscale effect may not be obtained.
[0007] Therefore, nano-scale fine particles are being considered. For example, Japanese Patent Laid-Open Publication No. 9-316206 (Patent Document 3) discloses a method in which polyamide pellets are dissolved in a solvent at high temperature and high pressure, and then the temperature or pressure is lowered to reduce the solubility and precipitate the polyamide as polymer particles. However, this method is difficult to dissolve para-type wholly aromatic polyamide resin, which has low solubility in solvents, and is therefore difficult to apply.
[0008] On the other hand, JP 2004-2731 A (Patent Document 4) discloses a method in which each monomer of an acid chloride of a wholly aromatic polyamide and a diamine compound is dissolved in a solvent, and then mixed and stirred with water and a solvent having a hydroxyl group that can dissolve in the solvent, and the polymer compound obtained by the reaction is precipitated in the form of particles. In this method, in order to reuse the fibrous product, which is the main form of wholly aromatic polyamide, in recycling, it is necessary to decompose it into monomer molecules by hydrolysis. In addition, the particle size obtained is about several hundreds of nm to several μm. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2011-168931 A [Patent Document 2] Special Publication No. 2019-511387 [Patent Document 3] Japanese Patent Application Publication No. 9-316206 [Patent Document 4] JP 2004-2731 A Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to solve the problems in the prior art and to provide fine particles of para-type wholly aromatic copolyamide which are excellent in handleability, workability and recyclability. [Means for solving the problem]
[0011] As a result of intensive research into solving the above problems, the present inventors discovered that the above problems can be solved by using a para-type wholly aromatic copolyamide having a specific structure in the production of para-type wholly aromatic copolyamide particles, and thus completed the present invention.
[0012] That is, according to the present invention, 1. Particles comprising a para-type wholly aromatic copolyamide represented by the following formula (1), characterized in that Ar1 in the following formula (1) comprises a para-phenylenediamine component and at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, and 4,4'-oxydiphenylenediamine, the molar ratio of the para-phenylenediamine component to the at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, and 4,4'-oxydiphenylenediamine is 10:90 to 90:10, Ar2 in the following formula (1) comprises a terephthalic acid dichloride component, the weight average molecular weight of the para-type wholly aromatic copolyamide is 40,000 to 1,000,000, and the average particle size of the para-type wholly aromatic copolyamide particles is 5 to 500 nm. [ka] 2. The para-type wholly aromatic copolyamide particles according to the above item 1, wherein the average particle size of the para-type wholly aromatic copolyamide particles is 8 to 300 nm. 3. The para-type wholly aromatic copolyamide particles according to the above item 1, wherein the average particle size of the para-type wholly aromatic copolyamide particles is 10 to 150 nm. 4. A compound resin comprising the para-type wholly aromatic copolyamide particles according to item 1 above. 5. A method for producing para-type wholly aromatic copolyamide particles, comprising contacting para-type wholly aromatic copolyamide fibers having a single yarn fineness of 20 dtex or less with an ionic liquid in a mass ratio of 0.5:99.5 to 10:90 to obtain a mixture, kneading the mixture under shear stress while heating it to 60°C or higher to produce an ionic liquid solution of para-type wholly aromatic copolyamide, and then adding water or an alcohol as a poor solvent to the ionic liquid solution of para-type wholly aromatic copolyamide with stirring. 6. The solubility parameter δt of the ionic liquid calculated by the molecular contribution method is 37 (J / cm 3 ) 1 / 26. A method for producing para-type wholly aromatic copolyamide particles according to 5 above, wherein the imidazolium-based ionic liquid is one of the above. 7. The method for producing para-type wholly aromatic copolyamide particles according to the above 6, wherein the ionic liquid is 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium methylphosphonate, 1-ethyl-3-methylimidazolium chloride, or 1-butyl-3-methylimidazolium chloride. 8. The solubility parameter δt of the ionic liquid by the molecular contribution method is 27 (J / cm 3 ) 1 / 2 The method for producing para-type wholly aromatic copolyamide particles according to the above item 5, in which the phosphonium-based ionic liquid is used; And, 9. The method for producing para-type wholly aromatic copolyamide particles according to the above item 8, wherein the ionic liquid is tributyl(ethyl)phosphonium diethylphosphate, tributyl(methyl)phosphonium dimethylphosphate, or trihexyl(tetradecyl)phosphonium chloride. is provided. Effect of the Invention
[0013] According to the present invention, fine particles having excellent heat resistance can be obtained. In addition, since the polymer solution is stable, a polymer having a low to high degree of polymerization can be obtained compared to polyparaphenylene terephthalamide, and a polymer solution of para-type wholly aromatic copolyamide fibers can be easily obtained without using alkali, which contributes to reducing the environmental load during production and simplifying the recovery process. In addition, since the para-type wholly aromatic copolyamide fibers once molded into fibers are redissolved and used, it is possible to reduce the use of fossil fuels through recycling. The resulting fine particles of para-type wholly aromatic copolyamide can be used as an additive for compounds or resins to improve heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below.
[0015] <Para-type wholly aromatic copolyamide> The para-type wholly aromatic copolyamide of the present invention is a polymer in which two or more divalent aromatic groups represented by the chemical formula (1) are directly linked by amide bonds. 1 Formula (2) and formulas (3) to (5) are mixed, and Ar 2 A wholly aromatic copolyamide having the formula (2) can be used.
[0016] [ka]
[0017] [ka]
[0018] Of the above-mentioned wholly aromatic copolyamides, it is necessary to use wholly aromatic copolyamides in which the mixture ratio of formula (2) and formulas (3) to (5) is 90:10 to 10:90. Among these wholly aromatic copolyamides, Technora (manufactured by Teijin Limited) is one that has already been industrialized.
[0019] <Production of para-type wholly aromatic copolyamide solution> In the present invention, the polymerization solution for the polymerization of the para-type wholly aromatic copolyamide may be an aprotic polar solvent such as N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), dimethylacetamide (DMAc), dimethylformamide (DMF), dimethylsulfoxide (DMSO), etc. Among these, N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), and dimethylacetamide (DMAc) are preferred, and N-methyl-2-pyrrolidone (NMP) and dimethylacetamide (DMAc) are more preferred.
[0020] In these aprotic polar solvents, salts of alkali metal halides or alkaline earth metal halides can be used as dissolution aids. Examples of alkali metal halides that can be used include lithium chloride, potassium chloride, and lithium bromide. Examples of alkaline earth metal halides that can be used include calcium chloride and magnesium chloride. The amount of dissolution aid used is preferably 5.0% by mass or less relative to the solvent, and more preferably 3.0% by mass or less.
[0021] Next, the monomers constituting the polymer are dissolved in an aprotic polar solvent or an aprotic solvent in which a dissolving aid has been dissolved. In this case, two diamine components are used. One is a paraphenylenediamine component, and the other is at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, or 4,4'-oxydiphenylenediamine, and they are dissolved so that the molar ratio (paraphenylenediamine component):(at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, or 4,4'-oxydiphenylenediamine) is 10:90 to 90:10.
[0022] Then, terephthalic acid dichloride is added as an acid chloride to the obtained solution so that the molar ratio of the diamine component to the acid chloride component becomes 100:88 to 100:100, and polymerization is carried out. A part of these monomers can be substituted with an electron-withdrawing group such as a halogen or a cyano group.
[0023] <Molecular weight of polymer> The weight-average molecular weight (Mw) of the para-type wholly aromatic copolyamide obtained by the above method must be 40,000 to 1,000,000. If the weight-average molecular weight (Mw) is 40,000 or less, it will not be possible to form threads in the subsequent spinning process. On the other hand, if the weight-average molecular weight exceeds 1,000,000, the viscosity of the dope will be too high, resulting in poor productivity.
[0024] <Other polymerization conditions, etc.> In order to improve the solubility of the resulting wholly aromatic copolyamide polymer, a suitable amount of a generally known inorganic salt may be added before, during, or at the end of the polymerization. Examples of such inorganic salts include chlorides of alkali metals such as lithium chloride, sodium chloride, and calcium chloride, and chlorides of alkaline earth metals such as magnesium chloride and calcium chloride. Of these, lithium chloride and calcium chloride are preferred.
[0025] The ends of the para-type wholly aromatic copolyamide can also be blocked using a terminal blocking agent, such as phthalic acid chloride and its substituted derivatives, aniline and its substituted derivatives, etc. In order to capture acids such as hydrogen chloride that are produced, aliphatic or aromatic amines, quaternary ammonium salts, etc. can also be used in combination.
[0026] After completion of the reaction, a basic inorganic compound such as sodium hydroxide, potassium hydroxide, calcium hydroxide, calcium oxide, etc. may be added, if necessary, to carry out a neutralization reaction. After the neutralization reaction, the precipitated salt is preferably removed through a filtration process. The polymer solution obtained by the above method maintains a solution state at 0 to 130° C., and therefore can be used as a dope for spinning as it is.
[0027] <Preparation of polymer solution (dope)> The method for preparing a polymer solution (dope) containing a para-type wholly aromatic copolyamide and a solvent is not particularly limited, and any known method can be used.
[0028] Examples of the solvent used in preparing the polymer solution (dope) include N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), dimethylformamide (DMF), dimethylsulfoxide (DMSO), and N-methylcaprolactam (NMC). The solvent may be one type alone or a mixed solvent of two or more types. Furthermore, the solvent used in the polymerization of the para-type wholly aromatic copolyamide may be used as it is.
[0029] The concentration of the polymer in the polymer solution (dope) is preferably 2 to 12% by mass. If the concentration is less than 2% by mass, the viscosity is too low, and the process is not stable when the polymer is subsequently coagulated and isolated, which is not preferred. If the concentration is more than 12% by mass, the polymer is not completely dissolved and precipitates, which is not preferred.
[0030] <Coagulation method> In the present invention, the polymer solution (dope) obtained above is wet-coagulated to form yarn, and the composition of the coagulation liquid is preferably a poor solvent for para-type wholly aromatic copolyamide. The composition of the coagulation liquid does not necessarily have to be a single one, and may be, for example, a mixed solution of NMP and water. From the viewpoint of the efficiency of solvent recovery, the higher the NMP concentration in the coagulation bath composition (NMP / water), the more preferable, and the NMP concentration is preferably 20% or more. More preferably, it is 25% or more.
[0031] <Other processes> After the filaments are pulled out of the coagulating solution, they are washed with water to gradually remove the solvent. For this purpose, the temperature of the washing bath is preferably 60° C. or less. After washing with water, the fiber is dried at a temperature of 100° C. or higher, and then stretched as necessary to form an oriented yarn, which is then subjected to a drying process and other steps to obtain the final fiber yarn.
[0032] As a method of drawing, not only water washing drawing and boiling water drawing in a coagulated yarn state, but also heating drawing in a dry yarn state can be performed. There is no particular restriction on the draw ratio, but it is preferably at least 6 times or more, and more preferably 8 times or more. By controlling the draw ratio, it is possible to control the elongation and strength of the obtained para-type wholly aromatic copolyamide fiber. In addition, by employing sequential drawing, it is possible to improve the drawing stability.
[0033] <Redissolving of para-type wholly aromatic copolyamide fiber> In the present invention, the fiber yarn obtained by the above-mentioned method is redissolved. In this case, it is preferable to use, as the fiber yarn, waste fiber that has become waste yarn during the manufacturing process or that has been mixed with other fibers to be used as spun yarn or filament for woven or knitted fabrics and then discarded.
[0034] For example, when waste yarn or fiber waste is used as the yarn to be redissolved, it is preferable to cut long fibers and short fibers for ease of handling in a kneader. The preferred fiber length is 51 mm or less, more preferably 0.5 to 30 mm, and even more preferably 0.5 to 10 mm. The shorter the fiber length, the greater the contact area with the solvent, which is preferable. The cutting method is to use a guillotine cutter, a rotary cutter, a fiber cutter for wool, or the like.
[0035] The fineness of the fiber used for redissolution must be 20 dtex or less, preferably 10 dtex or less, and more preferably in the range of 0.5 to 10 dtex. If the fineness is more than 20 dtex, the fiber is not completely dissolved and tends to remain.
[0036] When cutting, moisture can be added to prevent scattering, but it is necessary to dry it before dissolving. It is preferable to control the moisture content to within 10% under temperature conditions of 100°C or higher. If it is more than 10%, it will not dissolve properly, which is not recommended.
[0037] For the redissolution, a known mixer can be used, such as a single-shaft mixer, a ribbon mixer, a planetary mixer, etc. Among these, it is preferable to select a planetary mixer.
[0038] In dissolving, the ionic liquid is charged into a mixer, and then the para-type wholly aromatic copolyamide fiber yarn or cut yarn and powdered wholly aromatic copolyamide polymer are dispersed and brought into contact with the ionic liquid to form a mixture, which is then kneaded under shear stress while heating to 60° C. or higher. The heating temperature must be 60° C. or higher. A temperature of 80° C. or higher is more preferable because this can shorten the dissolution time.
[0039] As a result of investigating the ionic liquid that dissolves the fully aromatic copolyamide used in the above redissolution, the solubility parameter by the molecular contribution method was found to be 37 (J / cm 3 ) 1 / 2 The above imidazolium ionic liquid is one of the preferred ionic liquids. The cationic species of the ionic liquid is preferably an imidazolium ion in which R1 in molecular formula (6) is a methyl group and R2 is an alkyl group having 1 to 10 carbon atoms. More preferably, the carbon number is 2 to 8. If the carbon number exceeds 10, the viscosity becomes too high, and the viscosity of the obtained wholly aromatic copolyamide solution becomes too high, which is not preferred.
[0040] [ka]
[0041] Examples of anion species include halides such as F, Cl, and Br, acetate ions, alkyl phosphate ions, and alkyl phosphonate ions. Among these, acetate ions are preferred. Although the combination of these cations and anions is arbitrary (hereinafter, a space is inserted between the cation species and the anion species to distinguish them), 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium methylphosphonate, 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, and the like can be used alone or in combination of two or more. Among these, 1-ethyl-3-methylimidazolium acetate is particularly preferred from the viewpoint of solubility and the viscosity of the obtained fully aromatic copolyamide solution.
[0042] As a result of examining other ionic liquids to be used in the present invention, it was found that the solubility parameter was 27 (J / cm 3 ) 1 / 2 The above phosphonium-based ionic liquid is another preferred ionic liquid.
[0043] The cationic species of the ionic liquid is preferably a phosphonium ion in which R1 in molecular formula (7) is a methyl group or an ethyl group, and R2, R3, and R4 are alkyl groups having from 1 to 10 carbon atoms. If the carbon number exceeds 10, the viscosity becomes too high, and the viscosity of the obtained wholly aromatic copolyamide solution becomes too high, which is not preferred.
[0044] [ka]
[0045] Examples of anion species include halides such as F, Cl, and Br, acetate ions, alkyl phosphate ions, and alkyl phosphonate ions. Among these, acetate ions are preferred. Although the combination of these cations and anions is arbitrary (hereinafter, a space is inserted between the cation species and the anion species to distinguish them), one or more of tributyl(ethyl)phosphonium diethylphosphate, tributyl(methyl)phosphonium dimethylphosphate, and trihexyl(tetradecyl)phosphonium chloride can be suitably used. Among these, tributyl(ethyl)phosphonium diethylphosphate is particularly preferred from the viewpoint of solubility and the viscosity of the obtained fully aromatic copolyamide solution.
[0046] The mass ratio of the para-type wholly aromatic copolyamide fiber to the ionic liquid is 0.5:99.5 to 10:90. When the mass ratio of the para-type wholly aromatic copolyamide is less than 0.5% by mass, the amount of the para-type wholly aromatic copolyamide solution is too small when used as a spinning dope, making industrial production difficult. On the other hand, when the mass ratio of the para-type wholly aromatic copolyamide is more than 10% by mass, the viscosity becomes too high to make a spinning dope. The preferred mass ratio of the para-type wholly aromatic copolyamide to the ionic liquid is 0.5:99.5 to 8:92, and the more preferred mass ratio is 0.5:99.5 to 5:95.
[0047] In the present invention, water or alcohols can be used as a coagulation liquid for the para-type wholly aromatic copolyamide solution using the ionic liquid. That is, water or alcohols are added as a coagulation liquid to the ionic liquid solution of the para-type wholly aromatic copolyamide in a shear flow field caused by stirring to obtain a coagulated body.
[0048] An example of equipment that can obtain such a product is a submerged disperser. Representative types of submerged dispersers include high-speed shear agitators, colloid mills, roll mills, high-pressure jet dispersers, ultrasonic dispersers, container-driven mills, and media agitation mills. Among these, high-speed shear agitators, colloid mills, high-pressure jet dispersers, and ultrasonic dispersers are preferred for the purpose of avoiding contamination by foreign matter. A high-speed shear agitator is a dispersion device that uses high-speed shear flow in a narrow gap between a high-speed rotor and a head, and various types of equipment can be used.
[0049] At the laboratory level, it can be used by adding water little by little while rotating a magnetic stirrer or a single-shaft stirring blade at high speed. At the industrial level, it can be made with the "Super Shear Mixer" made by Satake Multimix, the "Clearmix" made by M Technique, the "Filmix" made by Primix, and the "Max Blend" made by Sumitomo Heavy Industries Process Equipment Co., Ltd. Colloid mills are dispersions by high-speed shear flow in the narrow gap between a high-speed rotating disk and a fixed disk, and can be made at laboratory to industrial levels using equipment such as the "Super Mass Colloider" and "Hyper Mass Colloider" made by Masuko Sangyo, and the "Aruria" made by M Technique. High-pressure jet dispersers disperse the processing liquid by high-pressure jetting it and colliding it with a fixed plate or with other processing liquids. Examples of high-pressure jet dispersers include the "Star Burst" made by Sugino Machine, the "Nano Vaita" made by Yoshida Kikai Kogyo, and the "G-smasher" made by Ricks, and can be made at laboratory and industrial production levels. These are used during solidification. They can also be reused to redisperse after solidification. These devices may also be used in combination.
[0050] It is essential that the average particle diameter of the thus obtained para-type wholly aromatic copolyamide particles of the present invention is 5 to 500 nm. The average particle diameter is preferably 8 to 300 nm, more preferably 10 to 150 nm. If the average particle diameter is less than 5 nm, it becomes difficult to knead the particles into the resin of the compound. On the other hand, if the average particle diameter exceeds 500 nm, the particles will not function as a nanoscale material.
[0051] In addition, it is essential that the weight-average molecular weight of the para-type wholly aromatic copolyamide constituting the para-type wholly aromatic copolyamide particles is 40,000 to 1,000,000. If the weight-average molecular weight is less than 40,000, it becomes difficult to form fibers, and it becomes difficult to obtain the fine particles of the present invention. On the other hand, if the weight-average molecular weight exceeds 1,000,000, not only is it difficult to form fibers, but it is also difficult to redissolve.
[0052] Furthermore, since a resin containing the para-type wholly aromatic copolyamide particles of the present invention as an additive has excellent heat resistance and moldability, the para-type wholly aromatic copolyamide particles of the present invention can be suitably used as an additive for compound resins. EXAMPLES
[0053] The present invention will be described in detail below with reference to examples and comparative examples, but the scope of the present invention is not limited to the following examples and comparative examples. In addition, each physical property in the examples was measured by the following methods.
[0054] The present invention will be described in more detail with reference to the following examples and comparative examples. However, these examples and comparative examples are provided to aid in understanding the present invention, and are not intended to limit the scope of the present invention.
[0055] (1) Observation of particle size using a microscope Para-type wholly aromatic copolyamide fine particles were diluted 1000 times with isopropanol, left to stand overnight, and the resulting supernatant was cast and dried to prepare a sample for observation under an electron microscope (SEM). The particle diameters of 20 particles observed were measured, and the average value was taken as the particle diameter.
[0056] (2) Molecular weight measurement The weight average molecular weight (Mw) and the molecular weight polydispersity (Mw / Mn) were measured by gel permeation chromatography (GPC) under the following measurement conditions. Device name: High-performance liquid chromatograph LC-20A series Column oven: CTO-20A Mobile phase: NMP Autosampler: SIL-20AHT LC workstation:LC solution Flow rate: 0.3ml / min Differential refractometer detector: RID-10A Oven temperature: 60℃ Molecular weight standard: Polystyrene
[0057] <Example 1> [Aramid fiber manufacturing] N-methyl-pyrrolidone (NMP) was placed in a reaction vessel, and p-phenylenediamine and 3,4'-diaminodiphenyl ether were weighed out and dissolved in equimolar amounts. Terephthalic acid dichloride was weighed out and added to this diamine solution in an equimolar amount relative to the total molar amount of diamines. After the reaction was completed, the mixture was neutralized with calcium hydroxide to obtain a 6% by mass solution of para-type wholly aromatic copolyamide. The molecular weight of the obtained polymer was 700,000.
[0058] The obtained polyparaphenylene-3,4'-oxydiphenylene-terephthalamide solution was used as it was, and spun from a spinneret (hole diameter 0.3 mmφ, number of holes 100) through an air gap of 10 mm between the spinneret face and the coagulation bath into a coagulation bath containing an NMP aqueous solution (NMP concentration: 40 mass%, temperature: 20°C) as a coagulation liquid (semi-dry, semi-wet process). Subsequently, the pulled-up coagulated yarn was washed with water at 60°C, dried by contact with a drying roller at 120°C for 25 seconds, and hot-drawn 10 times to obtain a wholly aromatic copolyamide fiber (copolyparaphenylene-3,4'-oxydiphenylene-terephthalamide fiber) with a single yarn fineness of 1.67 dtex. Among the fibers produced by this method, fiber waste (single filament fineness 1.5 dtex) that could not be used for products due to abnormal fineness was cut into 3 mm pieces using a guillotine cutter and used for remelting.
[0059] [Remelt] The fiber scraps cut into 3 mm pieces were dried at 120°C for 2 hours. 4,950 g of 1-ethyl-3-methylimidazolium acetate and 50 g of the dried fiber scraps were placed in a planetary mixer and kneaded under shear stress at 80°C for 1 hour in a nitrogen atmosphere. The resulting para-type wholly aromatic copolyamide solution contained no undissolved matter and was a transparent dope.
[0060] [Creating fine particles] 1-Ethyl-3-methylimidazolium acetate was added so that the para-type wholly aromatic copolyamide in the para-type wholly aromatic copolyamide solution became 1 mass %, and then 2 g was placed in a screw bottle. While rotating at 500 rpm with a magnetic stirrer, 2 mg of water was added in an amount of 1.5 times the mass with a micropipette to coagulate and precipitate the para-type wholly aromatic copolyamide in the polymer solution.
[0061] The aqueous solution of the para-type wholly aromatic copolyamide in the ionic liquid was then filtered, and the filtrate was mixed with water, stirred, and filtered again. This washing and filtering process was repeated a total of four times, and the filtrate was left to stand overnight at room temperature and naturally dried, and the particle size was observed with an electron microscope. The average particle size of the obtained para-type wholly aromatic copolyamide particles was 57 nm.
[0062] <Example 2> Spinning was carried out in the same manner as in Example 1, except that the molecular weight of the polymer was 40,000. The molecular weight was adjusted by changing the ratio of the total molar amount of diamines, p-phenylenediamine and 3,4'-diaminodiphenyl ether, to the molar amount of acid chloride, according to the method described in JP 2012-167387 A. The fiber waste of 16.7 dtex generated during this process was redissolved in the same manner as in Example 1 to produce fine particles. The average particle size of the obtained para-type wholly aromatic copolyamide particles was 22 nm.
[0063] <Example 3> The same procedure as in Example 1 was repeated, except that the amount of water added was 20 mg at a time using a micropipette. The average particle size of the resulting para-type wholly aromatic copolyamide particles was 220 nm.
[0064] <Example 4> Example 2 was carried out in the same manner as in Example 1, except that the concentration at the time of redissolution was 9% by mass. The average particle size of the obtained para-type wholly aromatic copolyamide particles was 405 nm.
[0065] <Example 5> The same procedure as in Example 1 was repeated except that the ionic liquid used was changed to tributyl(ethyl)phosphonium diethyl phosphate. The average particle size of the obtained para-type wholly aromatic copolyamide particles was 340 nm.
[0066] <Example 6> The same procedure as in Example 1 was repeated, except that the diamines used were p-phenylenediamine and 4,4'-oxydiphenylenediamine. The molecular weight of the resulting polymer was 680,000. The average particle size of the resulting para-type wholly aromatic copolyamide particles was 54 nm.
[0067] <Example 7> The same procedure as in Example 1 was repeated, except that the diamines used were p-phenylenediamine and 3,3'-oxydiphenylenediamine. The molecular weight of the resulting polymer was 540,000. The average particle size of the resulting para-type wholly aromatic copolyamide particles was 48 nm.
[0068] <Comparative Example 1> A para-type wholly aromatic copolyamide solution with a concentration of 6% by mass was obtained by the same method as in Example 1. Next, this solution was diluted with NMP to a concentration of 1% by mass to obtain a stock solution for obtaining fine particles without fiberization.
[0069] [Creating fine particles] The above stock solution was charged into a mixer, and while the mixer having a uniaxial anchor blade was rotating at 500 rpm, 20 mg of water was added in an amount 1.5 times the mass of the stock solution at a time while the mixer was rotating at 500 rpm, thereby coagulating and precipitating a para-type wholly aromatic copolyamide.
[0070] After that, the mixed solution of this para-type wholly aromatic copolyamide in NMP and water was filtered, water was added to the filtrate, stirred, and filtered again. This washing and filtering process was repeated a total of four times, and the filtrate obtained was left at room temperature overnight and naturally dried. The obtained polymer was light brown in color. When observed under an electron microscope, no fine particles were confirmed.
[0071] <Comparative Example 2> The same procedure as in Example 1 was repeated except that the ionic liquid used was changed to NMP. During redissolution, the fiber was observed to swell, but it did not dissolve, and it was not possible to form fine particles.
[0072] <Comparative Example 3> In Example 1, the same procedure as in Example 1 was carried out except that the molecular weight of the polymer was 20,000. The molecular weight adjustment was carried out by changing the ratio of the total molar amount of diamines, p-phenylenediamine and 3,4'-diaminodiphenyl ether, and the molar amount of acid chloride, according to the method described in JP 2012-167387 A. The same procedure as in Example 1 was attempted to form fibers, but fibers could not be formed.
[0073] The results of Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Table 1.
[0074] [Table 1] [Industrial Applicability]
[0075] INDUSTRIAL APPLICABILITY According to the present invention, fine particles of para-type wholly aromatic copolyamide excellent in handleability, workability and recyclability can be obtained, and therefore the present invention has high industrial applicability and extremely great industrial value.
Claims
1. Particles containing a para-type wholly aromatic copolyamide represented by the following formula (1), 1 comprises a paraphenylenediamine component and at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, and 4,4'-oxydiphenylenediamine, the molar ratio of the paraphenylenediamine component to the at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, and 4,4'-oxydiphenylenediamine is 10:90 to 90:10, and Ar in the following formula (1) is 2 The para-type wholly aromatic copolyamide particles are characterized in that they are composed of a terephthalic acid dichloride component, the weight average molecular weight of the para-type wholly aromatic copolyamide is 40,000 to 1,000,000, and the average particle size of the para-type wholly aromatic copolyamide particles is 5 to 500 nm. 【Chemistry 1】
2. 2. The para-type wholly aromatic copolyamide particles according to claim 1, wherein the average particle size of the para-type wholly aromatic copolyamide particles is 8 to 300 nm.
3. 2. The para-type wholly aromatic copolyamide particles according to claim 1, wherein the average particle size of the para-type wholly aromatic copolyamide particles is 10 to 150 nm.
4. 2. A compound resin comprising the para-type wholly aromatic copolyamide particles according to claim 1.
5. The main component is a para-type wholly aromatic copolyamide represented by the following formula (1), 1 comprises a paraphenylenediamine component and at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, and 4,4'-oxydiphenylenediamine, the molar ratio of the paraphenylenediamine component to the at least one diamine component selected from the group consisting of 3,4'-oxydiphenylenediamine, 3,3'-oxydiphenylenediamine, and 4,4'-oxydiphenylenediamine is 10:90 to 90:10, and Ar in the following formula (1) is 2 a terephthalic acid dichloride component, the para-type wholly aromatic copolyamide having a weight average molecular weight of 40,000 to 1,000,000, is contacted with an ionic liquid in a mass ratio of 0.5:99.5 to 10:90 to obtain a mixture, and the mixture is kneaded under shear stress while heating to 60°C or higher to produce an ionic liquid solution of the para-type wholly aromatic copolyamide. Then, water or an alcohol is added as a poor solvent to the ionic liquid solution of the para-type wholly aromatic copolyamide with stirring. 【Chemistry 2】
6. The ionic liquid has a solubility parameter δt of 37 (J / cm 3 ) 1/2 The method for producing para-type wholly aromatic copolyamide particles according to claim 5, wherein the imidazolium-based ionic liquid is the above-mentioned imidazolium-based ionic liquid.
7. 7. The method for producing para-type wholly aromatic copolyamide particles according to claim 6, wherein the ionic liquid is 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium methylphosphonate, 1-ethyl-3-methylimidazolium chloride, or 1-butyl-3-methylimidazolium chloride.
8. The ionic liquid has a solubility parameter δt of 27 (J / cm 3 ) 1/2 The method for producing para-type wholly aromatic copolyamide particles according to claim 5, wherein the phosphonium-based ionic liquid is the above-mentioned phosphonium-based ionic liquid.
9. 9. The method for producing para-type wholly aromatic copolyamide particles according to claim 8, wherein the ionic liquid is tributyl(ethyl)phosphonium diethylphosphate, tributyl(methyl)phosphonium dimethylphosphate, or trihexyl(tetradecyl)phosphonium chloride.
Citation Information
Patent Citations
Production of polyamide particle
JP1997316206A
Polyamide fine particles and its manufacturing method
JP2004002731A
Method for producing nanofiber
JP2011168931A
Gels and nanocomposites containing ANFS
JP2019511387A